Live working. Protective clothing against the thermal hazards of an electric arc. Test methods. Method 1: Determination of the arc rating (ELIM, ATPV and/or EBT) of clothing materials and of protective clothing using an open arc Part 1-1, (16th September 2019) - British Standards Institution,
No abstract available